2016
DOI: 10.1007/s00784-016-1919-8
|View full text |Cite
|
Sign up to set email alerts
|

Complications of endodontically treated teeth restored with fiber posts and single crowns or fixed dental prostheses—a systematic review

Abstract: A correlation between the failure rates of fiber posts and the type of prosthetic restorations just like SCs and FDPs cannot be found to date. Further randomized controlled clinical studies are required to achieve evidence-based conclusions, particularly about the use of fiber posts with FDPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
2
36
0
5
Order By: Relevance
“…Stress analysis showed FRC post and core to have the most similar stress pattern to natural tooth. This result is similar to other studies that have shown fiber posts in non-weakened teeth to exhibit normal tooth like stresses 19,20 . This may be due to similar modulus of elasticity which allowed the post to transmit the stresses like normal dentin and avoid areas of extreme stress concentration 21 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Stress analysis showed FRC post and core to have the most similar stress pattern to natural tooth. This result is similar to other studies that have shown fiber posts in non-weakened teeth to exhibit normal tooth like stresses 19,20 . This may be due to similar modulus of elasticity which allowed the post to transmit the stresses like normal dentin and avoid areas of extreme stress concentration 21 .…”
Section: Discussionsupporting
confidence: 92%
“…Endodontic treatment causes further loss of tooth structure due to endo procedures that weaken the tooth. Extensive loss of tooth structure presents a problem in retention of coronal restoration as well as fracture proneness due to weakened state 2 . In many cases, posts combined with cores are the solution to the retention problem especially when most or all of the coronal portion is lost.…”
Section: Introductionmentioning
confidence: 99%
“…However, using GFP in enlarged roots can be a challenge since the post is not completely adapted at coronal level. The thick layer of resin cement in this condition increases the risk to failure as a consequence of debonding or decementation (6).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of studies has been compared different types of prosthetic crowns about resistance to fracture and compression, success and survival (6,8). The porcelain-fused-to-metal crowns are materials widely used for restoration of endodontically treated teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The most common mode of failure for FRC posts is still loss of retention e.g. debonding from the post space 25,26) . Besides the difficulties of light transmission when luting FRC posts, there are many other problems related to the bonding of FRC posts.…”
Section: Discussionmentioning
confidence: 99%